A comparison between different definitions of contrast-induced acute kidney injury for long-term mortality in patients with acute myocardial infarction. (June 2020) - Lei, Li; Xue, Yan; Guo, Zhaodong; Liu, Bowen; He, Yibo; Song, Feier; Liu, Jin; Sun, Guoli; Chen, Liling; Chen, Kaihong; Huang, Zhidong; Ying, Ming; et al.
Highlights: CI-AKI is associated with prognosis in AMI patients irrespective of its definitions. CI-AKIC (Scr elevation ≥ 25% in the first 72 h) had the highest prevalence (18.77%) CI-AKIA (Scr elevation ≥ 50%/ ≥0.3 mg/dL in the first 72 h) had the highest PAR. Abstract: Background: Few studies have demonstrated the association between contrast-induced acute kidney injury (CI-AKI) and long-term mortality and explored which definition of CI-AKI accounts for most long-term deaths among patients with acute myocardial infarction (AMI). Therefore, we aimed to evaluate this association and compared the population attributable risks (PARs) of three CI-AKI definitions. Methods: We analyzed 1300 consecutive AMI patients undergoing angiography in Guangdong Provincial People's Hospital. The endpoint was all-cause mortality. CI-AKI was evaluated according to three definitions: (1) CI-AKIA, with a serum creatinine elevation ≥ 50% or ≥ 0.3 mg/dL from baseline in the first 72 h after procedure; (2) CI-AKIB, ≥ 0.5 mg/dL in 72 h; (3) CI-AKIC : ≥ 25% in 72 h; multivariable Cox analysis was conducted to evaluate the association between CI-AKI and long-term mortality. PARs of CI-AKI under different definitions were calculated with their odds ratios and prevalence among our cohort. Results: During the median follow-up period of 7.0 (5.5; 8.7) years, CI-AKI was significantly associated with poorer outcome regardless of the definition (adjusted hazard ratios: 1.417–2.711). Among the three definitions of CI-AKI, the prevalence was the highest for CI-AKIC (18.77%), and PAR was the highest for CI-AKIA (11.62%, 95% CI: 4.99–19.71), followed by CI-AKIB (9.20%, 95% CI: 4.22–16.00) and CI-AKIC (7.26%, 95% CI: 0.21–15.62). Conclusions: Our results suggested that CI-AKI is associated with long-term mortality in patients with AMI irrespective of its definitions. Cardiologists and studies regarding long-term prognosis should pay more attention to the presence of CI-AKI, especially CI-AKIA with the highest PAR.